2011
DOI: 10.1111/j.1528-1167.2011.03015.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the evolution of depression after epilepsy surgery

Abstract: SUMMARYPurpose: Both neurobiologic and psychosocial factors have been proposed to account for the high prevalence of depression surrounding epilepsy surgery. Using a prospective longitudinal approach, this study aimed to profile the evolution of depression after epilepsy surgery at multiple time points, including early and longer-term follow-up. We also sought to identify neurobiologic and psychosocial predictors of depression before and after surgery, including whether patients undergoing mesial temporal lobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 47 publications
(62 reference statements)
5
46
1
6
Order By: Relevance
“…In 2011, Wrench et al [46] followed 60 epileptics for 12 months after surgery and found that the prevalence of postoperative major depression (MD) was increased with time, but was still lower than the preoperative prevalence (30% vs 43%). In 2015, Barbieri et al [47] followed 248 PWE for 12 months after epilepsy surgery and found that 27% of patients experienced postoperative depression, 3 patients committed suicide after the end of the study, and one was diagnosed with de novo depression within 6 months after surgery.…”
Section: Retated Factors Of Depression After Epilepsy Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…In 2011, Wrench et al [46] followed 60 epileptics for 12 months after surgery and found that the prevalence of postoperative major depression (MD) was increased with time, but was still lower than the preoperative prevalence (30% vs 43%). In 2015, Barbieri et al [47] followed 248 PWE for 12 months after epilepsy surgery and found that 27% of patients experienced postoperative depression, 3 patients committed suicide after the end of the study, and one was diagnosed with de novo depression within 6 months after surgery.…”
Section: Retated Factors Of Depression After Epilepsy Surgerymentioning
confidence: 98%
“…In 2011, Wrench et al [46] found that 8% (5/60) of patients had de novo major depression. In 2011, Barbieri et al.…”
Section: Manifestation Of Depression After Epilepsy Surgerymentioning
confidence: 98%
“…For example, in a study of 60 PWE undergoing a temporal lobectomy (38 had a resection of mesial structures, and 22 had resection of temporal lateral neocortical structures) (19), a lifetime history of depression was identified in 43% of patients, with no difference between those who had mesial and those who had temporal lateral resections. In the 12 months after surgery, 20 patients (33%) experienced an MDE (occurring in the first 3 postsurgical months in 70% and persisting for at least 6 months in 65% of patients).…”
Section: Iatrogenic Psychiatric Adverse Eventsmentioning
confidence: 99%
“…32,33 Most depressive episodes are diagnosed in the first 3 months and persist for at least 6 months, with rates of depression steadily declining across a 24-month follow-up period. 33 Surgical resections disrupting mesial temporal structures increase the risk of de novo depression after surgery.…”
Section: Original Articlementioning
confidence: 98%
“…33 Risk factors for depression after surgery include a positive preoperative history of psychological disturbances and poor postoperative family support. 32 Globally, there is considerable variability in the psychiatric evaluation and follow-up of patients in epilepsy surgery programs. However, the existing literature suggests heightened risk for psychological comorbidity in patients with epilepsy who are surgically managed.…”
Section: Original Articlementioning
confidence: 99%